Da vida psíquica às formas de sofrer na cidade: experiências de sofrimento produzidas pelo isolamento social no contexto da pandemia por Covid-19 - Alves, Erinaldo Domingos (2024)
This dissertation evidence our effort to congregate the Public Health and Critical Urban Geography. Since emergency of the Covid-19 pandemic and its social isolation, we observe that these phenomena cause deep transformations in the urban way of life, stimulating crisis in the economic, political, social and public health context and allegedly changing the dinamic and perception of the time and space, as well as the way of subjectivation of city dwellers. In this sense, we seek to comprehend, based on people’s experiences, how the pandemic and the social isolation influenced the human life producing psychological suffering in the city of Fortaleza, Ceará. In fact, we proposed a extension of concept of space- time compression, originally created by British geographer David Harvey in the Critical Urban Geography in discussion about the capitalism, to think a notion of space-time compression articulated to the pandemic’s phenomenon and social isolation how an contribution to the Public Health. This extension led us to conceive the concepts of space- time compression, space-time decompression, life compression and life decompression, which effected in our study for reports of experiences of psychological suffering amid social isolation. Therefore, in the case of qualitative health research inscribed in the hermeneutic and materialist tradition, we conducted nine in-depth interviews with people over 18 years who lived the social isolation, being him working in person or home-office. The invite was made by means of a virtual questionnaire shared in social medias as Instagram and WhatsApp. In light of maximum variation criterion, we understand people of different: ages, gender, social classes, race, family composition, occupation and residents at different neighborhoods of Fortaleza, with the purpose of giving us one interview in order to reveal your experiences of psychological suffering amid social isolation and Covid-19 pandemic. Once transcribed, the interviews were subjected to an intersectional analysis in light of pluralistic approach to theory verification and generation, providing us examine the operationalization of the compression of life theory under implications of social isolation in the context of the Covid-19 pandemic. As a result, we found that the characters interviewed actually suffered psychological suffering of some nature, thus producing repercussions on their psychological life, improving the theoretical-conceptual apparatus previously generated. Finally, we presume to have provided Public Health with a theoretical overview, based on empirical knowledge, that allows it to be critically articulated with the metamorphoses suffered by the city and by human subjectivity after the resurgence of the pandemic and its social isolation and any other phenomena that affect public space, interrupting the permanence of life.